Nickel Content in Plants and Soil: The Case of Mine Tailing Sites in Bato-Bato Narra Palawan, Philippines - Acero, Liwayway Hubo (Institut Pertanian Bogor (IPB University), 2023)
Forests once deforested through mining losses its rich biodiversity. The re-opening of open-pit mining corporation in 2011, in the small village of Bato-Bato, Narra, Palawan had caused deforestation, floods, and low rice harvest. This study determined the nickel content in topsoil and native dominant plants in mine-tailings. Field data collection and laboratory analysis methods were used in this study. Nickel content in topsoil (2 kg replication-1 site-1) was analyzed using X-ray Flourescence (XRF). Inductively Coupled-plasma–Optical Emission Spectrometry (ICP-OES) determine nickel in dominant plants (200 g replication-1 site-1). Normality of data was determined by Pearson coefficient of skewness test. Significant difference on the nickel content in plant tissues was analyzed using Kruskal Wallis test, analysis of variance, and Tukey post hoc test for nickel in soil. Native dominants are National Seed Industry Council Rice cultivar 218, Philippine Seed Board Rice cultivar 18, and carabao grass. The nickel content in native dominant plants is higher in comparison with the average nickel content in plant tissues and the nickel content in topsoil is high in comparison with the average nickel content a topsoil should contain. Prevention of leaching of nickel during flood is recommended.